The Factors Contributing to the Decline in Community Trust in the Jokowi Administration's Government (2019-2024) - Marjan Miharja; Yastuty Handalya; Gunawan Nahrawi; Rahmat Dwi Putranto; Ryan Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study investigates the discrepancy between what should have happened during the development of the omnibus law on the work of the work and the policies relating to the Covid-19 epidemic in Indonesia and what really occurred. When the Omnibus Law and policies in the Pandemic Covid-19 are supposed to be a powerful solution to the problem, reality transforms into a field of new issues that generate a flood of negative comments from diverse individuals, resulting in a loss of faith in the government. The Omnibus Law and Covid-19 policies, which the Government and Parliament interpret as a progressive breakthrough for resolving multisectoral problems during the presidency of President Joko Widodo, are interpreted differently by some community circles and academics as laws and disabled policies, both formal and material. As a result, the aim of this study is to investigate the essence of Omnibus Law and Covid-19 policies, which have created a challenge for the Indonesian country by eroding community faith in the government.